The effects of family relationships on vocational college students’ mental health - Du, Yunpeng; Ma, Jiayue; Fu, Mengying; Yan, Mengyin (Frontiers in Psychology, 2026)
IntroductionUnder conditions of normalized pandemic prevention, family relationships have significantly impacted vocational students’ mental health. However, the underlying emotional regulation mechanisms remain unclear. Therefore, this study investigated how emotion regulation and self-efficacy mediate the impact of family relationships on vocational students’ mental health.MethodsUsing random sampling, we surveyed 2,026 students at a Chinese vocational college (November 2022), employing validated Chinese versions of the Emotion Regulation Questionnaire, Public Health Emergencies Questionnaire, Regulatory Emotional Self-efficacy Scale, and the Familial Aptitude and Cohesiveness Scale II.ResultsAll factors were significantly correlated (p < 0.05). Expressive suppression positively predicted mental health (β = 0.155, t = 4.787, p < 0.001), while self-efficacy for managing negative emotions negatively predicted mental health (β = −0.249, t = 7.446, p < 0.001). Family relationships induced mental health both directly and indirectly through emotion regulation.DiscussionFamily relationships impact mental health via two pathways: directly and through emotion regulation mechanisms—particularly expressive suppression and the management of negative emotions. These findings highlight the mediating role of emotional regulation, offering evidence to support family-centered psychological interventions in vocational education settings.